2021
DOI: 10.32872/spb.4389
|View full text |Cite
|
Sign up to set email alerts
|

Social distancing from foreign individuals as a disease-avoidance mechanism: Testing the assumptions of the behavioral immune system theory during the COVID-19 pandemic

Abstract: Topics of prejudice, discrimination, and negative attitudes toward outgroups have attracted much attention of social scientists during the COVID-19 pandemic, as the preference for social distancing can originate from the perception of threat. One of the theoretical approaches that offers an explanation for avoidance tendencies is the behavioral immune system theory. As a motivational system that aims to identify and avoid pathogens, the behavioral immune system has been shown to be triggered by various cues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Consistent with this, above and beyond strong effects of in-party favoritism/out-party derogation, participants who were dispositionally high in disease avoidance motivation—even Republican participants—believed Republicans to be more likely to infect others and felt more disgust toward them. Broadly, this is in line with research showing that people who dispositionally perceived a greater threat from COVID-19 reported greater preferred social distance from foreigners (Szymkow et al, 2021) and from Asian targets in the United States during the early stage of COVID-19 (Reny & Barreto, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this, above and beyond strong effects of in-party favoritism/out-party derogation, participants who were dispositionally high in disease avoidance motivation—even Republican participants—believed Republicans to be more likely to infect others and felt more disgust toward them. Broadly, this is in line with research showing that people who dispositionally perceived a greater threat from COVID-19 reported greater preferred social distance from foreigners (Szymkow et al, 2021) and from Asian targets in the United States during the early stage of COVID-19 (Reny & Barreto, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this, above and beyond strong effects of in-party favoritism/out-party derogation, participants who were dispositionally high in disease avoidance motivation-even Republican participants-believed Republicans to be more likely to infect others and felt more disgust toward them. Broadly, this is in line with research showing that people who dispositionally perceived greater threat from COVID-19 reported greater preferred social distance from foreigners (Szymkow et al, 2021) and from Asian targets in the United States during the early stage of COVID-19 (Reny & Barreto, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…considering any pandemic as a direct trigger for the BIS (see Ackerman et al, 2021), recent research suggests that the COVID-19 pandemic had noticeable effects on BIS-related factors (Schaller et al, 2021;Szymkow et al, 2021). 3.…”
Section: Discussionmentioning
confidence: 99%
“… 2. Although, we assume that exposure to the COVID-19 pandemic threat elicits emotions, we are well aware that the BIS has deep evolutionary roots. Even though we should be careful about considering any pandemic as a direct trigger for the BIS (see Ackerman et al, 2021), recent research suggests that the COVID-19 pandemic had noticeable effects on BIS-related factors (Schaller et al, 2021; Szymkow et al, 2021). …”
mentioning
confidence: 99%